Revisiting the dynamics of car cabin environment and driver comfort - Alkaabi, Khaula; Raza, Mohsin (Frontiers in Built Environment, 2022)
Revisiting the dynamics of the car cabin environment and its impact on driver comfort is essential, as these concepts have not been explored in recent years. Older methods of assessing driver comfort and cabin environments require elaborate experimental settings and prolonged engagement of study participants, making repeatability difficult. Therefore, this study develops a model for study models the car cabin environment based on temperature, humidity, and CO2 levels using a thermal imager, an air quality device, and open-source temperature and humidity data. This study also determines whether the impact of the cabin thermal environment on driver comfort (skin dryness, eye fatigue, body fatigue, and body heat) can be quantified based on driver perceptions. The study results showed that body fatigue decreased from 4.2 to 2.7 when the average relative humidity is reduced from 37.2% to 24.2%, and the temperature dropped from 41.8°C to 40.0°C. Notably, the impact of air temperature on the cabin thermal environment was 1.8 times stronger than that of the car skin temperature. Cabin temperature was found to be a better predictor of driver (dis)comfort than cabin humidity and CO2 levels. A 10 min exposure to summer heat in the UAE was found to have a significant effect on drivers’ perceptions of body fatigue, body heat, and eye fatigue. Overall, these findings have implications for car cabin ergonomics and future thermal comfort research.